Comparison of Clopidogrel and Ticlopidine/Ginkgo Biloba in Patients With Clopidogrel Resistance and Carotid Stenting - Chung, Jong-Won; Kim, Suk Jae; Hwang, Jaechun; Lee, Mi Ji; Lee, Jun; Lee, Kyung-Yul; Park, Man-Seok; Sung, Sang Min; Kim, Keon Ha; Jeon, Pyoung; Bang, Oh Young (Frontiers in Neurology, 2019)
Background and Purpose: Patients undergoing carotid artery stenting (CAS) who show low responsiveness to clopidogrel may have a higher risk of peri-procedural embolic events. This study aimed to compare the effectiveness and safety of clopidogrel and ticlopidine plus Ginkgo biloba in clopidogrel-resistant patients undergoing CAS. Methods: In this multi-center, randomized, controlled trial, we used platelet reactivity test to select patients undergoing CAS who showed clopidogrel resistance, and compared treatments using clopidogrel and ticlopidine plus ginkgo. The primary outcome was the incidence of new ischemic lesion in the ipsilateral hemisphere of CAS. Detection of microembolic signal on transcranial Doppler was the secondary outcome. The clinical outcomes were also monitored. Results: This trial was discontinued after 42 patients were randomized after preplanned interim sample size re-estimation indicated an impractical sample size. The primary endpoint occurred in 12/22 patients (54.5%) in the clopidogrel group and 13/20 patients (65.0%) in the ticlopidine–ginkgo group (P = 0.610). No significant differences in the presence of microembolic signal (15.0% vs. 11.8%, P = 0.580), clinical outcomes (ischemic stroke or transient ischemic attack, 0.0% vs. 5.5%; acute myocardial infarction 0.0% Vs. 0.0%; all-cause death, 4.5% vs. 0.0%), or incidence of adverse events were found in the two groups. In terms of resistance to clopidogrel, treatment with ticlopidine–ginkgo significantly increased the P2Y12 Reaction Units (difference, 0.0 [−0.3–3.0] vs. 21.0 [6.0–35.0], P < 0.001]. Conclusions: In patients who showed clopidogrel resistance, ticlopidine–ginkgo treatment was safe and increased P2Y12 Reaction Units; however, compared to clopidogrel, it failed to improve surrogate and clinical endpoints in patients undergoing CAS. This multimodal biomarker-based clinical trial is feasible in neurointerventional research. Clinical Trial Registration: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02133989.